Maternal age and adverse perinatal outcomes in a birth cohort (BRISA) from a Northeastern Brazilian city - Eduardo Durans Figuerêdo; Fernando Lamy Filho; Zeni Carvalho Lamy; Antônio Augusto Moura da Silva (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2014)
PURPOSE:To verify the existence of associations between different maternal ages and the perinatal outcomes of preterm birth and intrauterine growth restriction in the city of São Luís, Maranhão, Northeastern Brazil.METHODS:A cross-sectional study using a sample of 5,063 hospital births was conducted in São Luís, from January to December 2010. The participants comprise the birth cohort for the study "Etiological factors of preterm birth and consequences of perinatal factors for infant health: birth cohorts from two Brazilian cities" (BRISA). Frequencies and 95% confidence intervals were used to describe the results. Multiple logistic regression models were applied to assess the adjusted odds ratio (OR) of maternal age associated with the following outcomes: preterm birth and intrauterine growth restriction.RESULTS:The percentage of early teenage pregnancy (12-15 years old) was 2.2%, and of late (16-19 years old) was 16.4%, while pregnancy at an advanced maternal age (>35 years) was 5.9%. Multivariate analyses showed a statistically significant increase in preterm births among females aged 12-15 years old (OR=1.6; p=0.04) compared with those aged 20-35 years. There was also a higher rate in preterm births among females aged 16-19 years old (OR=1.3; p=0.01). Among those with advanced maternal age (>35 years old), the increase in the prevalence of preterm birth had only borderline statistical significance (OR=1.4; p=0.05). There was no statistically significant association between maternal age and increased prevalence of intrauterine growth restriction.